PS-C36-1: CLINICAL INERTIA IN THE HYPERTENSIVE PATIENTS TREATED BY HYPERTENSION SPECIALISTS. (January 2023) - Arakawa, Kimika; Imazu, Rina; Morinaga, Yuki; Tominaga, Mitsuhiro; Tsuchihashi, Takuya
Abstract : Background: Only about 30% of hypertensive patients in Japan is reported to have properly controlled blood pressure (BP). The clinical inertia (Inertia) seems to be one of the factors behind the inadequate BP control. Purpose: We investigate the achievement rate of the BP lowering target in 2020 for outpatients in the division of hypertension, and confirm the prevalence of inertia as a possible factor for the failure to achieve their BP targets. Methods: Subjects were 517 outpatients (mean age 68.6 ± 13.2 years, 54% of women) who regularly visited the division of hypertension from March to September 2020 and took antihypertensive drugs prescribed by hypertension specialists. We calculated the average of office BP (OBP) in the two visits during the same period, and the average of home BP (HBP) for the three days before each two visits. In addition, we investigated the antihypertensive drugs taken during that period and complications such as diabetes and chronic kidney disease, and collected blood chemistry and urine test data. From these data, as of December 2021, the attending doctors determined whether each patient achieved the BP target according to the Japanese Society of Hypertension 2019 (JSH2019), and chose one reason from the options in the patients who failed to achieve target BP. Results: The target for OBP in all subjects was < 130/80 (48%),  < 140/90 (140 group, 15%),  < 140/90 mandatory, and < 130/80 if tolerable (37%). The percentage of those who achieved each OBP target was 48% (OBP achievers, N = 246). As a result of investigating the reason for the OBP non-achievement (N = 273) by the attending doctors, 20% answered "judged to be the optimal BP level (Optimal)", 20% answered "due to the white coat effect ", and then "Inertia" was the next highest at 14%. Regarding the achievement rate of HBP for OBP achievers, 36% did not measure HBP, 38% achieved < 135/85 or < 130/80 (HBP 135), and 26% (N = 65) did not achieve it. Among the HBP 135 other than the 140 group (N = 66), the unachieved rate of < 125/75 was 58% (N = 38). The reasons for non-achievement of HBP (N = 103 in total), "Optimal" was the most common answer (42%), followed by "Inertia" (27%). Conclusion: Inertia existed as a factor explaining insufficient BP control even in the patients treated by hypertension specialists. From now on, in order to increase the rate of achieving the BP target, we should make an effort to overcome inertia.